Cryopreservation of botanical seeds of 10 wild potato species – a long-term viability monitoring study over the next 256 years at the International Potato Center (CIP) - Vollmer, R.; Soto-Torres, J.; Espirilla, J.; Espinoza, A.; Villagaray, R.; Mello, A.; Azevedo, V.C.R. (2025)
Cryopreservation is considered as the most effective and cost-efficient ex situ conservation method for the long-term conservation of clonally propagated crops. Beyond this, cryopreservation can play an important role for the conservation of orthodox seeds, as a safety backup and complementary conservation method for seeds with a shorter lifespan (<15 years). CIP has set up a long-term viability monitoring experiment with 10 wild potato species, and two accessions per specie, to compare the germination rate of seeds stored under traditional conditions (-20°C) and in cryopreservation (180 to -196°C). A set of 2500 seeds (5-6% seed humidity) were processed for each accession, of which 1250 seeds were stored at -20°C and -180 to -196°C, respectively. After one month of storage, a set of 150 seeds were germinated for each of the two storing temperatures. Additional samples of 100-150 seeds of each accession and treatment will be rewarmed and germinated after 2, 4, 8, 16, 32, 64, 128, and 256 years of storage. After one month in liquid nitrogen, no significant differences were observed between the germination rates of seeds stored at -20°C (93.2%) and in cryopreservation (95.4%). The study has been started in June 2023, and it is planned to expand it over the years to 50 wild potato species, using the same systematical approach. The experiment will provide valuable information about the maximum possible conservation period of orthodox botanical seeds under cryopreservation and at -20°C. Theoretically it is expected that the metabolic processes within seeds stored at -20°C, although very slowly, occur at a multiple higher rate compared to a storage temperature of -180 to -196°C. This may potentially permit to extend the conservation period of cryopreserved seeds to centuries.